- f-¹(x) = 69/5y
- f-¹(x) = 13 + 4y/(y + 10)
<h3>How to determine the inverse </h3>
The steps involved in determining the inverse of a function are;
- Replace f(x) with y in the equation describing the function
- Interchange x and y
- Solve for y
- Replace y by f-1(x)
If f(x) = 4/5x + 13
y = 4/5y + 13
y = 4 + 65 /5y
f^-1 = 4 + 65 /5y
f^-1(x)= 69/5y
If f(x)= 3/x+10 + 4
y = 3/y + 10 + 4
y = 3 + 4y + 10/(y + 10)
y = 13 + 4y/(y + 10)
f^-1(x) = 13 + 4y/(y + 10)
Thus, the inverse of the functions is 69/5y and 13 + 4y/(y + 10)
Learn more about functions here:
brainly.com/question/6561461
#SPJ1
Let x = 0. What do you get for y?
This gives you one point.
Then let x = 1. What do you get for y.
This gives you a second point.
Answer:
start by placing a point on 9
Step-by-step explanation:
then use "rise over run" ( which is ri/ru) so you go up 3, then over 5. (hope this helps!)
Answer:
Step-by-step explanation:
(51 miles)/(3 gal) = 19 miles/gal
The answer is 194.59
(72 x 100) / 37 = 194.59